Hubungan Antara Frekuensi Berenang Terhadap Kapasitas Paru Paru Perenang Di Kolam Renang Manahan Surakarta - Rillo Pambudhi, Risky; , Wahyuni, S,KM.,M.Kes (2016)
Background : The lungs are the organs that have a vital function in humans. Lung function as a tool of the human respiratory tract,which requires oxygen and removingcarbon dioxide is needed to run the normal functioning of cells in the body. The lungs have a good capacity to maintain physical health and physical enduance to maximum. Lung capacity that can either be done by sport or physical exercise. Exercise can increase lung capacity well among other things, running, jumping and swimming. At the time of exercising going cooperation body marked with changes in muscle strenght, muscle flexibility, speed of reaction. Swimming is one of aerobic exercise that also involves the entire body's main muscle and also give the overall result compared to other sport. At a time of increased lung capacity swim 2 fold compared with the rest. The frekuensi of swim that routine can provide goodresult on response of the body, including the heart of the lungs, peripheral blood vessels, muscle and the endocrine system. Research objectives: to describe the intensity of swimmers swim at Manahan. To describe the enormous lung capacity on the pool swimmer manahan. Knowing the relationship between swimming with lung capacity. Method: the type of research used in this study was anilisis correlation with cross sectional approach. The research design point approach means that every time the subject is only observed once and measurements of the status or variable character of the subject at the time of examination. Results: Based on research it can be concluded that there is a significant relationship between the frekuensi of swimming with the value of lung capacity on the swimmers in the pool Manahan Surakarta. Keywords: Frekuensi, Pool, Vital Capacity